The Molecular Weight of the Major Glycoprotein from the Human Erythrocyte Membrane - Grefrath, Stuart P. (1974)
The molecular weight of the major glycoprotein from the human erythrocyte membrane is 29,000, of which 55% is carbohydrate and 45% is protein. The binding of sodium dodecyl sulfate to this glycoprotein is anomalous when compared to water soluble proteins and leads to migration rates in sodium dodecyl sulfate-polyacrylamide gels that cannot be interpreted in terms of molecular weight. Anomalous sodium dodecyl sulfate binding may be a general characteristic of many intrinsic membrane proteins even if they are not glycoproteins, and such proteins are likely to have mobilities in sodium dodecyl sulfate-gel electrophoresis that do not correspond to the mobilities of water soluble proteins of identical molecular weight.